EFEKTIFITAS PERMAINAN TWISTER DALAM MENGENALKAN WARNA PRIMER PADA ANAK TUNAGRAHITA RINGAN KELAS DII/C DI SLB KASIH UMMI PADANG - Silvia Muclis (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrak: The background of this study was mild mental retardation in a child class DII / C are not familiar with the primary colors. To improve the recognition of primary colors used mild mental retardation in children twister game. Based on the above problems, this study aims to prove whether the twister game can improve recognition of primary colors mild mental retardation in children in the class DII / C in SLB Kasih Ummi Padang. This type of research is that researchers use in the form of single-subject experimental research (SSR) with ABA design. Assessment in the study was measured by percentage. The results showed, mild mental retardation in a child's ability to know the basic color increases.   Kata kunci: Permainan Twister, Mengenalkan Warna Primer, Tunagrahita ringan